2',3',4'-Trihydroxychalcone changes estrogen receptor α regulation of genes and breast cancer cell proliferation by a reprogramming mechanism - Candice B. Herber; Chaoshen Yuan; Anthony Chang; Jen-Chywan Wang; Isaac Cohen; Dale C. Leitman (BMC, 2022)
Abstract Background Menopausal hormone therapy (MHT) is recommended for only five years to treat vasomotor symptoms and vulvovaginal atrophy because of safety concerns with long-term treatment. We investigated the ability of 2',3',4'-trihydroxychalcone (2',3',4'-THC) to modulate estrogen receptor (ER)-mediated responses in order to find drug candidates that could potentially prevent the adverse effects of long-term MHT treatment. Methods Transfection assays, real time-polymerase chain reaction, and microarrays were used to evaluate the effects of 2',3',4'-THC on gene regulation. Radioligand binding studies were used to determine if 2',3',4'-THC binds to ERα. Cell proliferation was examined in MCF-7 breast cancer cells by using growth curves and flow cytometry. Western blots were used to determine if 2',3',4'-THC alters the E2 activation of the MAPK pathway and degradation of ERα. Chromatin immunoprecipitation was used to measure ERα binding to genes. Results The 2',3',4'-THC/E2 combination produced a synergistic activation with ERα on reporter and endogenous genes in human U2OS osteosarcoma cells. Microarrays identified 824 genes that we termed reprogrammed genes because they were not regulated in U2OS-ERα cells unless they were treated with 2',3',4'-THC and E2 at the same time. 2',3',4'-THC blocked the proliferation of MCF-7 cells by preventing the E2-induced activation of MAPK and c-MYC transcription. The antiproliferative mechanism of 2',3',4'-THC differs from selective estrogen receptor modulators (SERMs) because 2',3',4'-THC did not bind to the E2 binding site in ERα like SERMs. Conclusion Our study suggests that 2',3',4'-THC may represent a new class of ERα modulators that do not act as a direct agonists or antagonists. We consider 2',3',4'-THC to be a reprogramming compound, since it alters the activity of ERα on gene regulation and cell proliferation without competing with E2 for binding to ERα. The addition of a reprogramming drug to estrogens in MHT may offer a new strategy to overcome the adverse proliferative effects of estrogen in MHT by reprogramming ERα as opposed to an antagonist mechanism that involves blocking the binding of estrogen to ERα.